Impact of preoperative Prognostic Nutritional Index levels on morbidity in colorectal cancer surgery - Senger, Aziz Serkan; Dincer, Mursit; Uzun, Orhan; Gulmez, Selcuk; Avan, Deniz; Ofluoglu, Cem B.; Duman, Mustafa (Edizioni Luigi Pozzi, 2022)
Aim: The Prognostic Nutritional Index (PNI) is a valuable parameter that indicates the immunonutritional status of patients with malignant tumors. MATERIAL AND METHODS: Patients operated for colorectal cancer between January 2013 and December 2019 were analyzed retrospectively. The relationship between PNI and morbidity was investigated in the 314 patients included in the study. Based on previous studies, the PNI cutoff value was set at 45, and the patients were duly divided into two groups: PNI <45 and PNI >= 45. The demographic and clinicopathological characteristics, as well as postoperative complications in the two groups, were compared. RESULTS: There was no statistical difference in gender, localization, T stage, N stage, perineural invasion, lymphovascular invasion, stage, Ca19-9 values, and body mass index(BMI) between the two groups. In contrast, there was a statistically significant difference in age, complications, and CEA values. (p=0.008, p<0.001, p=0.043, respectively). The median age was lower in patients with high PNI scores than in the low PNI group (61 vs. 64 years). When the patients were examined for complications, 36 (37.1%) patients were observed in the high PNI group, compared to 155 (71.4%) in the low PNI group. In terms of overall survival, the mean lift expectancy was 68.112 +/- 2.646 months for patients with low PNI group, compared to 84.626 +/- 2.701 months in the high-PNI group, and the difference was statistically significant (p=0.001). CONCLUSION: This study's findings suggest that the preoperative Prognostic Nutritional Index may indicate postoperative complications and prognosis. The most significant benefit of this marker is that it can be improved preoperatively and practically.
Keywords: Colorectal Neoplasms; Morbidity; Nutritional Status